Self-Disclosure and Communication Security in Tinder Relationships: An Online Dating Study - Harahap, Hamida Syari (Universitas Semarang, 2023)
Introduction: The culture of dating has changed a lot, and young people today are more interested in finding romantic partners through online dating sites. This study aims to describe interpersonal relationships that are formed through an online dating application called Tinder. Methods: This study used a qualitative design with a phenomenological approach. Three users of the online dating application Tinder, namely two men and one woman, were selected purposively as research informants. Data collection was carried out virtually using interview techniques and observation of informant conversations on the dating application. Meanwhile, in-depth interview data were only obtained from research informants who actively used the application. To reduce research bias, the researcher conducted further data exploration by extending the research time and recording and collecting verbal and nonverbal data virtually. The data obtained were analyzed using NVivo12 software. Findings: These findings suggest that communication security in daring relationships is a concern for Tinder users. Furthermore, the study found that self-disclosure does not always guarantee privacy security in online interpersonal relationships. This study proves that the theory of self-disclosure contradicts the assumption of self-disclosure and privacy. Originality: The novelty of this study is that it brings together the concept of communication security with social media studies. Many studies place the concept of self-disclosure in relation to interpersonal communication and are studied using a quantitative approach. Meanwhile, this study places self-disclosure within the framework of communication security studies with mixed methods.